Role of Intraoperative Ultrasound in Minimizing Anaesthetic Exposure during High-Risk Gynecologic Surgeries - Nuzahat Nazar Cheema, Shazma Ejaz, Mamoona Shaikh, Summar Fatima, Saniya Naheed, Tahir Baig (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gynecologic surgeries with high risks are recommended to be linked with a long operating time and exposure to general anesthesia, which can negatively influence the outcomes during the perioperative period. There is a need to have strategies that are able to improve the level of precision and efficiency of surgery at no additional expense. Intraoperative ultrasound can offer real-time view of anatomy in the pelvic region and could lead to a decrease in the complexity and exposure to anesthetics. Objective: To determine the extent of intraoperative ultrasound in reducing the duration of operations and anesthetic exposure during high-risk gynecologic operations. Methods: This is a prospective comparative observational study that lasted six months in a tertiary care teaching hospital. One hundred and twenty women who were subjected to high-risk hysterectomy and laparoscopy surgery under general anesthesia were recruited and split into two equal groups. Group A was operated under the aid of intraoperative ultrasound and Group B was operated under the aid of intraoperative ultrasound. The two groups had the same standard surgical and anesthetic procedures. The total anesthesia time was the primary outcome, whereas the secondary outcomes were operative time and intraoperative anesthetic stability. Results: The two groups had demographic and clinical similarities in terms of baseline demographics and clinical characteristics. There was a significant difference in the mean operative time and total anesthesia time between intraoperative ultrasound and non-ultrasound groups. The number of patients who took extra anesthetic supplementation and intraoperative hemodynamic instability was less in the ultrasound-assisted group. There were no further expenses or complexities of using ultrasound. Conclusion: Intraoperative ultrasound is a useful and effective supplement to high-risk gynecologic surgeries, which has led to the lessening of the operating time and the exposure of anesthesia. Its regular implementation in some cases can enhance the efficiency of the peri-operative and safety of anesthetic care without raising the expenses of health care. Keywords: Intraoperative ultrasound; Gynecologic surgery; High-risk surgery; Anesthetic exposure.